Stress-Induced Hyperprolactinemia: Pathophysiology and Clinical Approach - Samara Levine; Ozgul Muneyyirci-Delale (Obstetrics and Gynecology International)
While prolactin is most well known for its role in lactation and suppression of reproduction, its physiological functions are quite diverse. There are many etiologies of hyperprolactinemia, including physiologic as well as pathologic causes. Physiologic causes include pregnancy, lactation, sleep-associated, nipple stimulation and sexual orgasm, chest wall stimulation, or trauma. Stress is also an important physiologic cause of hyperprolactinemia, and its clinical significance is still being explored. This review will provide an overview of prolactin physiology, the role of stress in prolactin secretion, as well as the general clinical approach to hyperprolactinemia.